The effect of natural antioxidants on quality and shelf life of beef and beef products - Horbańczuk, Olaf K. (Array, 2019)
Oxidation processes are the major cause of deterioration of meat quality and shelf life of meat products, leading to negative changes in nutritive value and in sensory and physicochemical properties of meat. Until now, the synthetic antioxidants like butylated hydroxyl anisole have been commonly used to prevent oxidation, which however may cause potential human health risks and increase toxicity of the product. However, natural antioxidant can be the alternative solution for this problem since plants and plant materials are rich in bioactive compounds (as natural antioxidants) with potential health beneficial effects. Moreover, the interest of consumers in using natural products is still increasing. There is an expectation of replacing synthetic antioxidants and preservatives by natural ones. Therefore, the aim of the present review is to provide information on the effect of natural antioxidants from vegetables and fruits like olives, pomegranate or grapes, and herbs and spices like rosemary, oregano, sage, black cumin or turmeric, rich in bioactive compounds on quality and shelf life of beef and beef products.